2013
DOI: 10.14202/vetworld.2013.874-878
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of haemoparasites in pet, working and stray dogs of Assam and North-East India: A hospital based study

Abstract: Aim: This research work is aimed to find out the prevalence of haemoparasitic infections in different categories of dogs.Materials and Methods: Out of 2104 dogs registered in the Teaching Veterinary Clinical Complex of the College of Veterinary Science, Khanapara, Guwahati during January 2009 to December 2010, blood of 424 cases suspected for haemoparasites on the basis of clinical history were microscopically examined in wet blood film and giemsa stained blood smears. Results:The prevalence was 57.31% in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 4 publications
2
12
1
Order By: Relevance
“…Prevalence of anaplasmosis in the present study was found similar with the findings of (Pennisi et al, 2012) who reported 38% prevalence of anaplasma. Findings of (Bhattacharjee and Sarmah, 2013) are not in agreement with current study and the possible reasons may be that (Bhattacharjee and Sarmah, 2013) reported only Anaplasma platys and did not reported Anaplasma phagocythophilum.…”
Section: Risk Factors For Haemo-parasitescontrasting
confidence: 94%
“…Prevalence of anaplasmosis in the present study was found similar with the findings of (Pennisi et al, 2012) who reported 38% prevalence of anaplasma. Findings of (Bhattacharjee and Sarmah, 2013) are not in agreement with current study and the possible reasons may be that (Bhattacharjee and Sarmah, 2013) reported only Anaplasma platys and did not reported Anaplasma phagocythophilum.…”
Section: Risk Factors For Haemo-parasitescontrasting
confidence: 94%
“…Dogs may also be infected with pathogenic haemoparasites including Babesia species (Nalubamba et al, 2011), Trypanosoma species (Keck et al, 2009), Leishmania spp., Hepatozoon spp., Ehrlichia spp., Anaplasma spp., Mycoplasma spp., (Haemobartonella spp.,) and Dirofilaria spp., which are transmitted through different arthropod vectors, including ticks, lice, triatomes, mosquitoes, tabanids and phlebotomine sandflies. They cause illnesses called canine vector-borne diseases (CVBD) in tropical and subtropical countries (Bhattacharjee & Sarmah, 2013), some of which are of zoonotic importance (Saritas et al, 2005). Incidences of haemoparasites in dogs have been reported in Vom, Nigeria (Kamani et al, 2011), where the prevalence of 42% was reported comprising mostly Babesia canis (27%).…”
Section: Introductionmentioning
confidence: 99%
“…However, Ehrlichia canis was seen in exotic breed of dog which may be attributed to breed susceptibility (Nyindo et al, 1980). Babesia canis and Hepatozoon canis has been documented to affect dogs in India (Bhattacharjee and Sarmah, 2013) and in Cape Verde (Gotsch et al, 2009). The presence of Babesia canis and Hepatozoon canis in our study may be attributed to the fact that the tick vector (Rhipicephalus sanguneus) occur in large numbers in Jos south almost all year round (Kamani et al, 2011).…”
Section: Discussionmentioning
confidence: 47%